Daily life in the Middle Ages - Newman, Paul B. (McFarland, 2001)
Provides information on the daily life of people during the Middle Ages, covering such topics as cooking, cleaning, clothing and dress, medicine, and leisure time.
Keywords: Geschichte 500-1500; Civilisation médiévale; Dagelijks leven; Histoire sociale - 500-1500 (Moyen Âge); Middeleeuwen; Moyen Âge; Stadscultuur; Vie rurale - Europe - Histoire - 500-1500 (Moyen Âge); Vie urbaine - Europe - Histoire - 500-1500 (Moyen Âge); Alltag; Alltag, Brauchtum; Geschichte; Mittelalter; Sozialgeschichte; Civilization, Medieval; Middle Ages; Social history -- Medieval, 500-1500; City and town life -- Europe -- History -- To 1500; Country life -- Europe -- History -- To 1500; Alltagskultur; Europe - Murs et coutumes; Europa; Europe -- Social life and customs